Integrating sustainable development, lean, and logistics concepts into a lean sustainable logistics model - Sooksiri Wichaisri (2018)
© 2017 Inderscience Enterprises Ltd. This paper presents to identify opportunities and gaps of research for the integration of sustainable development, lean, and logistics concepts into a lean sustainable logistics model. Conceptual evaluation is the first step to understand the main points and link each concept. These concepts consist of four components, including the goals, elements, benefits, and limitations of each. The three relationships investigated in this research consist of the interfaces of sustainable development and logistics management, sustainable development and lean concept, and lean concept and logistics management. Following the conceptual evaluations and interfaces among them, the three concepts are integrated into a lean sustainable logistics model. There are four stages, comprising discordant action, proficiency, cooperation, and interdependence, for analysing the constructed model combination of lean sustainable logistics. Then the lean sustainable logistics model can be synthesised for implementation in organisations to achieve long-term benefits.